Adivasis and the State Politics in Jharkhand. (June 2018) - Kumar, Sujit
This article attempts to analyse the political behaviour of the adivasi groups in Jharkhand as rooted in the interplay of their interactions with different religions, exposure to non-agricultural economic activities and diverse nature of association with the state. The questions considered for inquiry are: Is the political terrain in Jharkhand moving towards 'detribalization' of governance? And, what are the factors influencing the voting behaviour of the adivasis? The article argues that the ambivalences occupying the interstices of the intra-community political behaviour are crucial in deciphering the adivasi politics. Ostensibly, the political choices of the adivasi community are largely framed in accordance with their everyday interaction with the local state as well as remote experiences of the latter as evident in cases of resource grab. The article is based upon the close observation of events concerning adivasis, analysis of assembly election data as well as news in local and national newspapers.